Father's education and construct of the early adolescent's emotional intelligence - Naghavi, Fataneh; Redzuan, Ma'rof (Marsland Press, 2012)
The emotional intelligence structure is a concept with little empirical research, particularly in relation to the link between family circumstance and personality characters and with respect to family educational status of early adolescents. For this reason, the specific objective of this research is to determine the relationship between father’s education status and early adolescent’s emotional intelligence. The basic principles of Emotional Intelligence are identifying, managing, understanding, and regulating emotions. The present study was carried out among 234 Iranian students in the second and grades of guidance schools (age 12-15) in Tehran, Iran. The students (girls and boys) were clustered through random and multistage sampling. Data were collected using the family background questionnaire and Schutte’s (1998) Emotional Intelligence Scale. Results of multiple comparisons of LSD indicate that there is significant difference between groups of father’s education status. Consequently, multi comparisons of LSD confirmed the results of the ANOVA. The findings indicate that the early adolescents, whose fathers have higher level of education, have higher emotional intelligence.